Ethnic Koreans in China: Korean School Closings and Losing Korean Ethnicity - Yin, Yilin (fi=Turun yliopisto|en=University of Turku|, 2016)
Ethnic Koreans have been a successful model among China’s 55 ethnic minorities. Ethnic Koreans in China have achieved great success in their ethnic education, and have been maintaining their language through Korean schooling. Facing the economic and social changes in China, however, increasing numbers of Koreans parents tend to choose Han Chinese schooling over Korean one. The main purpose of this research is to explain why ethnic Korean schools in China is closing down. According to the analysis of data from the 1990, 2000 and 2010 Chinese population censuses, and interviews with fourteen ethnic Korean parents, low fertility, residential expansion, uncompetitive Korean schooling, and perceptional changes toward ethnic education are mainly responsible for the closing of Korean schools in China. These behavioral and perceptional changes in the Korean society have been accompanied by China’s market economy, rapid urbanization and globalization. Ever since the market economy was introduced in China and as more frequent contacts have been made between China and South Korea, mainstream society has been opening door for ethnic Koreans to achieve upward social mobility. In the process of integration to the mainstream, Korean education is declining, and ethnic Korean society is losing its countenance as an ethnic minority society in China.